THE DEVELOPMENT OF CONTROLLER STATE OF CHARGE OF THE BATTERY - Komarov, S. V.; Voskoboinikov, V. E.; Zaitsev, O. M.; Novikov, V. F. (Science and Transport Progress, 2006)
A flow diagram of a controlling device for the state of charge of storage battery is offered. The algorithms of functioning of comptroller and blocks are developed. Some methods of limitation of voltage increase on the accumulators are considered.